2017
DOI: 10.3390/ijms18112315
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Human Atherothrombosis: Sources, Markers and Therapeutic Targets

Abstract: Atherothrombosis remains one of the main causes of morbidity and mortality worldwide. The underlying pathology is a chronic pathological vascular remodeling of the arterial wall involving several pathways, including oxidative stress. Cellular and animal studies have provided compelling evidence of the direct role of oxidative stress in atherothrombosis, but such a relationship is not clearly established in humans and, to date, clinical trials on the possible beneficial effects of antioxidant therapy have provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 169 publications
(238 reference statements)
0
50
0
4
Order By: Relevance
“…Oxidative stress is also associated with inflammation and the development of atherosclerosis [68]. The increase in reactive oxygen species (ROS) production is produced in part by the activation of NADPH oxidases [69].…”
Section: Lesion Progressionmentioning
confidence: 99%
“…Oxidative stress is also associated with inflammation and the development of atherosclerosis [68]. The increase in reactive oxygen species (ROS) production is produced in part by the activation of NADPH oxidases [69].…”
Section: Lesion Progressionmentioning
confidence: 99%
“…Numerous studies showed that the AGEs and the advanced lipoxidation end products (ALEs) are involved in the development and progression of chronic degenerative diseases, including diabetes [28][29][30], cardiovascular diseases [29,31,32], neurological disorder [33,34], some types of cancer [35,36], and all those pathologies in which the mechanisms of oxidative stress are involved, as well as the senescence processes [33].…”
Section: Age's Biochemistrymentioning
confidence: 99%
“…Atherothrombosis is a complex and abnormal chronic inflammatory/immune arterial wall remodeling initiated by the deposition of lipids and oxidative stress followed by recruitment of circulating leukocytes, proliferative responses with atheromatous plaque growth, proteolysis, neo-angiogenesis, apoptosis, calcification, fibrosis, plaque rupture, and thrombosis (Martin-Ventura et al, 2017). While platelets play a central role in arterial thrombogenesis because of fast flow conditions, a thrombus developing on disrupted plaques regularly involves great quantities of fibrin (Figure 1).…”
Section: Biology Of Atherothrombosismentioning
confidence: 99%